2020
DOI: 10.1177/1756286420910310
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes from the global pharmacovigilance database on interferon beta-1b exposure

Abstract: Background: The goal of the present cohort study was to review outcomes of patients exposed to interferon beta-1b during pregnancy. Methods: Pregnancy cases with exposure to interferon beta-1b reported to Bayer’s pharmacovigilance (PV) database from worldwide sources from January 1995 through February 2018 were retrieved for evaluation. Only cases where pregnancy outcomes were unknown at the time of reporting (i.e. prospective cases) were included in the analysis of this retrospective cohort study. Results: As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous observational studies [9][10][11][12][13][14][15][16][17][18] and a large post-authorisation safety study (PASS) [19] in women with MS have reported no increase in the prevalence of adverse pregnancy outcomes after exposure to IFN-beta before or during pregnancy. Data from Finland, however, suggest that the prevalence of elective terminations for reasons other than foetal anomaly may be increased among pregnant women exposed to IFN-beta [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational studies [9][10][11][12][13][14][15][16][17][18] and a large post-authorisation safety study (PASS) [19] in women with MS have reported no increase in the prevalence of adverse pregnancy outcomes after exposure to IFN-beta before or during pregnancy. Data from Finland, however, suggest that the prevalence of elective terminations for reasons other than foetal anomaly may be increased among pregnant women exposed to IFN-beta [19].…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent pharmacovigilance data analysis by Hellwig et al revealed that the use of interferon beta-1b until conception and in the first pregnancy trimester is not linked to an increased risk of abnormal pregnancy outcomes compared with the general population. 63 Nevertheless, in general, caution is required when using DMDs in pregnant women or in women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…According to the United States Center for Disease Control and Prevention (CDC), health professionals should follow some recommendations when performing obstetric procedures in pregnant patients with confirmed or suspected COVID-19 diagnosis, from prehospitalization to discharge of the mother and baby. [51][52][53][54][55][56][57][58][59][60] It is worth mentioning that, in Brazil, the diagnosis in pregnant women must follow the same protocol for the general adult population and that attention should be paid to the signs and symptoms that demonstrate clinical severity. 46 Prehospital care includes notification of the obstetrics unit for the proper delivery room preparation, for the correct use of personal protective equipment (PPE) by the health professionals involved and conduct in accordance with biosafety rules.…”
Section: Maternal-fetal Carementioning
confidence: 99%